Present mind in aging brain: Neural associations of dispositional mindfulness in cognitive decline. (20th December 2022) - Sumec, Rastislav; Filip, Pavel; Vyhnalek, Martin; Katina, Stanislav; Hort, Jakub; Sheardova, Katerina
Abstract: Background: Subjects at risk of dementia, such as subjective cognitive decline (SCD) and mild cognitive impairment (MCI), present with specific clinical symptoms, as well as functional and structural changes within the brain. Dispositional mindfulness (DM) has been linked to better cognitive performance and is associated with activation and grey matter volume of specific brain regions. It is yet unknown how DM is related to cognitive and neural parameters of those at risk of dementia. Objective: To estimate the association of DM with cognitive functions, brain volumetry, functional connectivity and gray matter integrity in key regions relevant for cognition (hippocampus, anterior cingulate cortex) and self‐awareness (ventromedial prefrontal cortex (vmPFC), posterior cingulate cortex) in SCD and MCI subjects. Methods: 79 non‐demented older adults with memory complaints ((SCD = 48, MCI = 31) were assessed by neuropsychological tests, MRI volumetry, resting‐state fMRI‐derived connectivity and DTI. Dispositional mindfulness was examined with Breath Counting Task (BCT). Results: Participants with MCI showed significantly worse BCT performance in comparison to SCD (p˂0.001). In MCI, BCT performance was positively associated with connectivity (p˂0.001) and negatively related to mean gray matter diffusivity (p˂0.05) in vmPFC. No other significant associations were found between DM, MRI measures and neuropsychological variables in either group. Conclusion: Worse cognition in subjects at risk of dementia may be reflected in changes in DM. Lower connectivity and worse gray matter integrity of vmPFC in MCI could play a role in the worsening of DM in this population. Longitudinal studies are needed to further clarify the relatedness of DM and neural changes elicited by neurodegeneration in people at higher risk of dementia.